Effective telephoning - Comfort, Jeremy; York Associates (Oxford : Oxford University Press, 1996)
This book is divided into ten units which deal progressively with key aspects of telephoning from preparation through to making arrangements and closing calls.
Keywords: English language; Business English; Telephone; English language -- Business English; Telephone in business; Telephone etiquette